Strengthening Child Protection Systems Through Customary Law and Cultural Values in West Sulawesi - Sadat, Anwar; Haris, Abdul Gaffar; Baharuddin, A. Zamakhsyari (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This paper explores the integration of local laws and cultural values as a strategy to reduce violence against children in the districts of Polewali Mandar and Majene. The study emphasizes the importance of aligning formal legal frameworks with traditional customs, social norms, and cultural practices to enhance the effectiveness of child protection initiatives. By incorporating local values into these frameworks, communities can better engage with and support efforts to ensure the well-being and safety of children. Through case studies and interviews with local leaders, legal experts, and community members, the research demonstrates the positive outcomes of culturally sensitive legal integration. The findings indicate that respecting and incorporating local values into child protection policies significantly decreases instances of violence against children. The paper concludes that a comprehensive approach, combining both legal and cultural perspectives, is crucial for fostering a safe and supportive environment for children in these regions. https://dataroominfo.org/strategi-optimal-meraih-kemenangan-di-slot-gacor-panduan-terperinci/ https://dataroomllc.com/menelusuri-keberuntungan-panduan-lengkap-slot-online-di-kasino-indonesia/ https://dataroomnow.net/panduan-lengkap-slot-gacor-menemukan-keberuntungan-di-dunia-kasino-daring/ https://dataroomportal.com/menemukan-slot-gacor-strategi-paling-efektif-untuk-meningkatkan-peluang-menang-di-kasino-online/ https://dataroomstudio.com/panduan-lengkap-slot-gacor-rahasia-dan-strategi-terbaik-untuk-menang-di-kasino-online/ https://davidkaufmannchess.com/menemukan-slot-gacor-panduan-lengkap-untuk-pemain-kasino-online-di-indonesia/ https://deeminidachshunds.com/mengenal-slot-gacor-strategi-dan-keunggulan-dalam-permainan-kasino-daring/ https://digiw3.com/menelusuri-fenomena-slot-gacor-analisis-jitu-di-dunia-kasino-online/ https://djdataroom.com/mengapa-slot-gacor-menjadi-pilihan-utama-dalam-dunia-kasino-online-di-indonesia/ https://dreszorrilla.com/panduan-lengkap-menang-besar-di-slot-gacor-strategi-dan-tips-terbaik/